Analisis Dimensi Organisasi Pembelajaran Pengaruhnya Terhadap Kinerja Pegawai Perindustrian, Perdagangan dan Koperasi Kabupaten Pohuwato - Abdul Wahab Kadai; Moh. Rolli Paramata; Yakup Yakup (STKIP PGRI SITUBONDO, 2022)
This study aims to analyze the dimensions of the learning organization its influence on employee performance. The data used in this study is primary data sourced from filling out questionnaires. The research population is 54 employees using the census method. The analytical technique used to answer the research problem and test the hypothesis is multiple regression analysis. The data is processed using the Statistical Product Service Solution (SPSS) application. The findings of this study are (1) there is a positive and significant influence on the dimensions of personal expertise on employee performance, (2) there is a positive and significant influence on the dimensions of mental models on employee performance, (3) there is a positive and significant influence on the dimensions of shared vision on employee performance, ( 4) there is a positive and significant influence on the dimensions of team learning on employee performance, (5) there is a positive and significant influence on the dimensions of dialogue on employee performance. The dominant variable affecting employee performance is the team learning dimension.